Worries, Mental and Emotional health difficulties of Portuguese University students - Reis, Marta; Ramiro, Lúcia; Gaspar de Matos, Margarida (Advances in Social Sciences Research Journal, 2019)
The aim of this study was to reach an in-depth understanding on how Portuguese university students feel towards life in general, which are their worries, how often they feel worried, and how intense their worries are. Moreover, it was intended to identify the kind of psychosocial variables involved, strategies they use as well as which are the sources of their well-being. A total of 2991 university students, participated in the quantitative study and in the qualitative study, there were 50 participants between 18 and 35 years old. A significant minority of students got worried frequently, allowing their worries to interfere significantly in their lives. Gender and age differences were found. Having worries demonstrated to be relevant and negatively associated with young people’s perception of well-being, self-regulation and resilience; showing that the mental health of the Portuguese university students is at risk, mainly when their social emotional skills are underdeveloped.